FINDING MATRIX CONCEPTS BASED ON COGNITIVE LOAD THEORY ON MATHEMATICS LEARNING ABILITY TO IMPROVE MATHEMATICS LITERACY - Asmara, Andes Safarandes; Ardiyanti, Yusi; Suparman, Tarpan (JPI (Jurnal Pendidikan Indonesia), 2018)
This research aimed at improving mathematical literacy among vocational high school students. The subject was students in class X. This qualitative research used tests, observation sheets, questionnaires, and interviews. The result shows that there was a limitation in our brain to process complex contents. Therefore, according to cognitive load theory, in the studying process, the teacher should minimize intrinsic cognitive load and stimulate germane cognitive theory, thus improving students' literacy.